UNLAWFUL ACT IN TRANSFER OF RIGHTS TO INHERITANCE LAND THAT IS DAMAGEOUS TO THE HEIR (STUDY OF SUPREME COURT DECISION NUMBER: 1206 K/PDT/2020 DATED JUNE 3, 2020) - Anna Kholilah Daulay; Hasim Purba; Burhan Sidabariba; Edy Ikhsan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Article 02 of Law No. 5 of 1960 concerning the Basic Agrarian Law states that ownership rights can be transferred. In hte process of transferring ownership, legal disputes are often unavoidable. One such legal issue related to the transfer of ownership is highlighted in the Supreme Court Decision No. 1206 K/Pdt/2020, in conjunction with the Makasar High Court Decision No. : 504/PDT/2018/PT MKS, and the Makasar District Court Decision No : 4/Pdt.G/2018/PN.Mks. The decisions indicate that the Defendants committed an unlawful act that harmed the Plaintiff, who was the heir. These rulings show discrepancies and conflicts in the court's verdicts. This thesis aims to explore the following issues: the legality of gifts between spouses under the Indonesian Civil Code and hte Compilation of Islamic Law, hte legal resolution of inheritance land transfers involving unlawful acts, and the judicial considerations in ruling on disputes involving unlawful acts in inheritance land transfers that harm the heirs (Case Study of Supreme Court Decision No. : 1206 K/Pdt/2020 dated June 3, 2020). The research method used in this thesis is normative juridical research, which is descriptive-analytic. It employs a normative juridical approach and secondary data sources, including primary, secondary, and tertiary legal materials. The data collection techniques include literature review and document analysis. The research uses qualitative analysis to examine the legal materials, followed by deductive reasoning to draw conclusions and provide answers to the research problems. The findings of this study reveal that hte legitimacy of gifting land between spouses during the marriage is prohibited under Article 1678 of the Civil Code, whereas, under Article 78 of the Compilation of Islamic Law, such gifts are not prohibited. Dispute resolution in land ownership transfers involving unlawful acts can be carried out through mediation or legal proceedings in court. The legal basis for the judge's consideration is Article 283 Rbg/163 HIR, where the Plaintiff successfully proved the claims in the lawsuit through a deed of gift and witness testimony. As a result, the court ruled that the disputed land was an inheritance from the Plaintiff's mother, and it was proven that the Defendants had committed unlawful acts. It is recommended that the parties clarify the legal status of the inheritance land by filing a petition with the Religious Court to prevent future inheritance disputes. Additionally, regional officials, such as the sub-district head, village head, and PPAT (land deed officials), should thoroughly investigate hte objects and family history of the gift applicant to ensure legal certainty in future gift transactions.